Kangbainian Lotion Ameliorates Vulvovaginal Candidiasis in Mice by Inhibiting the Growth of Fluconazole-Resistant Candida albicans and the Dectin-1 Signaling Pathway Activation - Chen, Zewei; Luo, Tengshuo; Huang, Fengke; Yang, Fuzhen; Luo, Wenting; Chen, Guanfeng; Cao, Mengfei; Wang, Fengyun; Zhang, Jun (Frontiers in Pharmacology, 2022)
Vulvovaginal candidiasis (VVC) is an infectious disease caused by Candida species, which affects millions of women worldwide every year. The resistance to available antifungal drugs for clinical treatment is a growing problem. The treatment of refractory VVC caused by azole-resistant Candida is still facing challenges. However, research on new antifungal drugs is progressing slowly. Although a lot of reports on new antifungal drugs, only three new antifungal drugs (Isavuconazole, ibrexafungerp, and rezafungin) and two new formulations of posaconazole were marketed over the last decade. Chinese herbal medicine has advantages in the treatment of drug-resistant VVC, such as outstanding curative effects and low adverse reactions, which can improve patients' comfort and adherence to therapy. Kangbainian lotion (KBN), a Chinese herbal medicine formulation, has achieved very good clinical effects in the treatment of VVC. In this study, we investigated the antifungal and anti-inflammatory effects of KBN at different doses in fluconazole-resistant (FLC-resistant) VVC model mice. We further studied the antifungal mechanism of KBN against FLC-resistant Candida albicans (C. albicans) and the anti-inflammatory mechanism correlated with the dectin-1 signaling pathway. In vivo and in vitro results showed that KBN had strong antifungal and anti-inflammatory effects in FLC-resistant VVC, such as inhibiting the growth of C. albicans and vaginal inflammation. Further studies showed that KBN inhibited the biofilm and hypha formation, reduced adhesion, inhibited ergosterol synthesis and the expression of ergosterol synthesis-related genes ERG11, and reduced the expression of drug-resistant efflux pump genes MDR1 and CDR2 of FLC-resistant C. albicans in vitro. In addition, in vivo results showed that KBN reduced the expression of inflammatory factor proteins TNF-α, IL-1β, and IL-6 in vaginal tissues, and inhibited the expression of proteins related to the Dectin-1 signaling pathway. In conclusion, our study revealed that KBN could ameliorate vaginal inflammation in VVC mice caused by FLC-resistance C. albicans. This effect may be related to inhibiting the growth of FLC-resistance C. albicans and Dectin-1 signaling pathway activation.